SOSIALISASI MENINGKATKAN PENCEGAHAN PELECEHAN SEKSUAL DAN BAHAYA PENYALAHGUNAAN NARKOTIKA PADA PELAJAR DI TINGKAT KECAMATAN CIBEBER KOTA CILEGON - Hamdan Hamdan; Putri Raninda Isabililah; Ahmad Thomi Rafif; Nur Hasanah (Jurnal Abdimas Bina Bangsa, 2022)
Cibeber sub-district is a sub-district in Cilegon City, Banten Province, has an area of ​​3.13 km², a population of 2,014 people, consisting of 6 sub-districts including: Bulakan, Cibeber, Cikerai, Kaliimbang, Karangasem, and Kedaleman. Communities in Cibeber District still do not realize the importance of knowing and caring in preventing sexual harassment and the dangers of narcotics abuse in adolescents at the Cibeber District level. This is based on the high problem of sexual harassment and drug abuse in adolescents in Cibeber District. The purpose of this socialization is to increase public legal awareness of the crime of sexual violence and the dangers of narcotics abuse, especially among teenagers. In addition, the socialization carried out also aims to find out the forms of sexual violence or sexual harassment, and how to handle and report on criminal acts of sexual harassment, which is also useful for providing lessons regarding Law Number 12 of 2022 concerning Criminal Acts. Sexual Violence. Including to know the types of narcotics and the dangers resulting from drug abuse. The forms of sexual violence crimes include: non-physical sexual harassment, physical sexual harassment, forced contraception, forced sterilization, forced marriage, sexual torture, sexual exploitation, sexual slavery and electronic-based sexual violence. Based on these things, the problems that will be examined in this study aim to: 1). Increase public legal awareness regarding the prevention of sexual harassment and the dangers of narcotics in adolescents 2). Efforts to provide understanding and learning for adolescents in the face of preventing sexual harassment and the dangers of narcotics